Keratinocyte Monolayers on Hyaluronic Acid Membranes as "Upside-Down" Grafts Reconstitute Full-Thickness Wounds - Horch, Raymund E.; Wagner, Gilbert; Bannasch, Holger; Kengelbach-Weigand, Annika; Arkudas, Andreas; Schmitz, Marweh (Medical Science Monitor, 2019)
BACKGROUND Skin replacement by means of cultured epithelial keratinocytes is a well-accepted method. However, several clinical drawbacks of sheet autografts (CEA - cultured epithelial autografts) have stimulated various efforts to optimize cell culture and cell delivery. Recent developments include use of cell monolayers instead of a fully differentiated epithelium, as well as use of various biomaterials to grow and transport the cultured cells. To optimize the transfer of human keratinocytes directly to the recipient wound bed, we used an "upside-down" technique, delivering cultured cells directly to the wound with the carrier material on top. MATERIAL AND METHODS Subconfluent second-passage human keratinocyte monolayers on esterified hyaluronic acid membranes (KHAMC - Keratinocyte-Hyaluronic-Acid-Membrane-Composites) were transplanted either as upside-down grafts or as upside-up grafts onto standardized full-thickness wounds in athymic nude mice versus controls with the cell-free membrane alone. RESULTS In the upside-down group, 14 days after grafting, a multi-layered, differentiating epidermis was found, whereas the wounds in the upside-up group and in the control group were not completely closed up to day 21. Persistence of human keratinocytes was shown in the upside-down group only, from day 7 until day 35 after grafting. CONCLUSIONS This study confirms that upside-down grafting of subconfluent monolayers of serum-free cultured human keratinocytes on esterified hyaluronic acid membranes is a suitable means to transfer actively proliferative keratinocytes, and reduces wound contraction. Compared to standard grafting protocols of cultured epithelium, such as CEA sheet grafts, it is easier to apply, does not need enzymatic detachment of cells from the culture dish, and limits the number of production steps required.
CRIS-Team Scopus Importer:2019-09-17